Hydrocarbon and Fatty Acid Composition from Blowfly Eggs Represents a Potential Complementary Taxonomic Tool of Forensic Importance,. Issue 6 (10th July 2019) - Lunas, Belisa M.; de Paula, Michele C.; Michelutti, Kamylla B.; Lima‐Junior, Sidnei E.; Antonialli‐Junior, William F.; Cardoso, Claudia A. L.
Abstract: One of the most important contributions of forensic entomology is to assist criminal expertise to determine the postmortem interval, which depends on the duration of the immature stages of insects of forensic interest. On the other hand, the time of development of the different stages varies according to the species; therefore, its identification is essential. Currently, few studies have investigated the use of cuticular hydrocarbons, and none regarding fatty acids, as complementary taxonomic tools to expedite species identification. Therefore, we evaluated whether cuticular hydrocarbons together with fatty acids of eggs of flies of the family Calliphoridae, main group of forensic interest, can be used to distinguish species. The analyses were performed by chromatographic techniques. The results show that there are significant differences between the composition of cuticular hydrocarbons and fatty acids between species and, therefore, they can be used to provide a complementary taxonomic tool to expedite the forensic expertise.